ANALISIS EFEKTIVITAS FREE CASH FLOW TERHADAP FINANCIAL PERFORMANCE SERTA AGENCY COST SEBAGAI VARIABEL MEDIASI - Rifad Hidayah Pangestu; Dicky Jhoansyah; Asep Muhamad Ramdan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Manufacturing companies are one of the sectors that contribute to Indonesia’s economic growth. One of its components is the miscellaneous industry sector, which also plays a role in supporting national economic development. However, in recent years, this sector has experienced a decline in financial performance, as reflected by the decrease in Return on Assets (ROA). Financial performance is an important indicator used to assess a company’s ability to manage its resources efficiently in generating profits. This study aims to examine the effect of free cash flow on financial performance with agency cost as a mediating variable in miscellaneous industry sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This study employed a quantitative method with an explanatory approach. The data used in this study were obtained from the financial statements of miscellaneous industry sector companies listed on the Indonesia Stock Exchange during 2020–2024. The sample consisted of 25 companies or 125 observations selected using the purposive sampling technique. The data were analyzed using Structural Equation Modelling (SEM) based on Partial Least Square (PLS) with the assistance of SmartPLS 3 software. The results indicate that free cash flow has a positive and significant effect on agency cost, as evidenced by a coefficient value of 0.418 and a p-value of 0.020 < 0.05. Agency cost has a positive and significant effect on financial performance, as indicated by a coefficient value of 0.247 and a p-value of 0.012 < 0.05. Free cash flow also has a positive and significant effect on financial performance, as shown by a coefficient value of 0.288 and a p-value of 0.003 < 0.05. Furthermore, agency cost is proven to significantly mediate the effect of free cash flow on financial performance, as indicated by a coefficient value of 0.103 and a p-value of 0.031 < 0.05.